Expressed emotion moderates the effects of family-focused treatment for bipolar adolescents. - Miklowitz, D; Axelson, D; George, E; Taylor, DO; Schneck, C; Sullivan, A; Dickinson, L; Birmaher, B (2009)
OBJECTIVE: Family interventions have been found to be effective in pediatric bipolar disorder (BD). This study examined the moderating effects of parental expressed emotion (EE) on the 2-year symptomatic outcomes of adolescent BD patients assigned to family-focused therapy for adolescents (FFT-A) or a brief psychoeducational treatment (enhanced care [EC]). METHOD: A referred sample of 58 adolescents (mean age 14.5 +/- 1.6 years, range 13-17 years) with BD I, II, or not otherwise specified was randomly allocated after a mood episode to FFT-A or EC, both with protocol pharmacotherapy. Levels of EE (criticism, hostility, or emotional overinvolvement) in parents were assessed through structured interviews. Adolescents and parents in FFT-A underwent 21 sessions in 9 months of psychoeducation, communication training, and problem-solving skills training, whereas adolescents and parents in EC underwent 3 psychoeducation sessions. Independent "blind" evaluators assessed adolescents' depressive and manic symptoms every 3 to 6 months for 2 years. RESULTS: Parents rated high in EE described their families as lower in cohesion and adaptability than parents rated low in EE. Adolescents in high-EE families showed greater reductions in depressive and manic symptoms in FFT-A than in EC. Differential effects of FFT-A were not found among adolescents in low-EE families. The results could not be attributed to differences in medication regimens. CONCLUSIONS: Parental EE moderates the impact of family intervention on the symptomatic trajectory of adolescent BD. Assessing EE before family interventions may help determine which patients are most likely to benefit from treatment.